FISHERMANS’ PERCEPTION ABOUT THE MATERIAL AND IMPLEMENTATION PROGRAM OF FISHERY INVESTIGATION IN DOMPAS VILLAGE BUKIT BATU SUB-DISTRICT BENGKALIS DISTRICT RIAU PROVINCE - Agok Sandi Nayoan; Ridar Hendri; Kusai ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research had been conducted on 10-20 of august in 2015 at Dompas village, Bukit Batu sub-district, Bengkalis district, Riau Province. The methode which was used in this research is qualitative methode. This kind of methode was chosen because the way how to get the data or information directly from the area by emphasizing more on the aspect of face to face and listening directly to the informations or explanations. Fishermans’ perception on the material of the investigation program given had an influence on the real application in the area where the fisherman applied the recommendation of investigation team about the convension of terubuk fish. This program could also said that it did not take serious impact on fishermans’ revenue. The program conducted should be consistent in implementing. It means that the plan of program should be continously done. It is in order to make the fishermans able to understand well what they will be done for the future. Then, the team should frequently do such a coordination or reviewing in order to know how far the developmnet has been achieved after the fishery investigation in Dompas village, Bukti Batu sub-district, Bengkalis district, Riau Province. Keywords: Perception, material, Implementing, Investigation